Development of MS sugar beet hybrids with low content of K+ and Na+ - М. О. Корнєєва; М. В. Власюк; І. В. Власюк (Plant Varieties Studying and Protection)
On the basis of cyclic crosses, on the background of two pollen sterile testers, the combining ability for the content of K+ and Na+ ions of 20 pollinators with different levels of hibreeding (of Verkhnyachka, Lgov and Veseliy Podil origins) was studied. The pollinators were differentiated for their genetic value and the strategy for their further breeding improvement was established. Two hybrid combinations were found in which the low content of simultaneously 2 types of K + and Na+ ions was essentially proved. These characters in hybrids mostly depend on GCA of the pollinators.